The effectiveness of biofilter and density of different stocking in aquaponic resirculation systems in the integration of tilapia (Oreochromis niloticus L.) and pakchoy plants (Brassica rapa L.). Issue 1 (April 2020) - Munawarawanti, A E; Omar, S B A; Syamsuddin, R; Syaiful, S A; Ulfa, F; Dachlan, A
Abstract: The availability of land and water for the cultivation process is limited, thus aquaponics cultivation technique is necessary to be considered. This study aimed to determine the effectiveness of bio filter at different stocking densities and the effects on the growth of tilapia and pakchoy plants in aquaponic systems. This research was conducted at Romangpolong Village, Bontomarannu District, Gowa Regency, South Sulawesi, from August to October 2018. The study was conducted in the form of factorial experiment with two factors arranged according to a randomized block design. The first factor was the treatment of biofilter with bioball filter media which consisted of three levels: without bioball, 25 bioballs, 50 bioballs. The second factor was the density of fish stock consisting of two levels namely density of fish stocking with 6 fish per 50 L water per container and with 12 fish per 50 L water per container. The data were analyzed by analysis of variance followed by the Least Significant Difference test at the level of 5%. The results indicate that the interaction of 25 bioballs filter and the fish density of 6 fish per 50 L container produced the best water quality, thus can support the optimum metabolic process and producing the best growth and survival of fish reaching 100 % and was able to supply the nutrient needs of pakchoy plants. The best results of growth and production of pakchoy shown were leaf area of 70.22 cm 2 and fresh weight of 65.99 g/plant.